A GIS-AHP approach for determining the potential of solar energy to meet the thermal demand in southeastern Spain productive enclaves. (April 2023) - Romero-Ramos, J.A.; Gil, J.D.; Cardemil, J.M.; Escobar, R.A.; Arias, I.; Pérez-García, M.
Abstract: In this work, the potential of southeastern Spain to host solar thermal plants to meet the heat demands of its industrial enclaves is assessed and presented. For this, the generation of thermal energy for industrial uses in the medium temperature range is estimated, with special emphasis on those areas not connected to the thermal energy distribution networks. This region has been selected due to its high availability of solar resources, while forming a geographic area that presents numerous agrifood industries. These facilities, according to their temperature range heat demands for boiling, pasteurizing, and other food-related processes, are one of the best-suited sectors for the application of medium-temperature solar collectors, both parabolic trough and linear Fresnel. A Geographic Information System and the Analytic Hierarchy Process Method have been used for information management and decision making, respectively. A geographic database was built using layers provided by different information sources on climate, land characteristics and use, industrial activity, and energy infrastructures, including the distance to natural gas distribution pipelines as a specific criterion for decision making. The final result translates into a geographic suitability scale, which revealed that about 5 % ( 1482 km 2 ) of the total territory in southeastern Spain is highly suitable for the future development of productive enclaves fed by solar thermal installations, where it is estimated that the energy demand could be met in 42 % ( 9 . 5 TWh/y ) with parabolic trough and 65 % ( 14 . 7 TWh/y ) linear Fresnel collectors in areas with a score since 7 points. Highlights: Suitable areas to install solar heat for industrial processes. Combination of Analytic Hierarchy Process and Geographic Information Systems. Distance to natural gas distribution pipelines is the most determining criterion. Solar fraction for regional industrial heat demands of 42% (PTC) and 65% (LFC).